A robust surface with superhydrophobicity and underwater superoleophobicity for on-demand oil/water separation. Issue 36 (8th September 2021) - Zhao, Siyang; Liang, Yongmin; Yang, Yu; Huang, Jinxia; Guo, Zhiguang; Liu, Weimin
Abstract : Superhydrophobic and underwater superoleophobic surface combine the superiorities of the two opposite wettabilities. Abstract : Superhydrophobic and underwater superoleophobic surface combine the superiorities of the two opposite wettabilities. Generally, such a surface is constructed by hydrophilic areas and hydrophobic areas treated with fluorine-containing modifiers. However, the surface energy in a narrow range and poor bonding force between water-loving and water-repelling components make the surface fragile and its wettability unstable. Herein, we present a strategy to fabricate a robust surface with superhydrophobicity and underwater superoleophobicity. Hydrophilic aluminum phosphate as a binder can strongly interact with superhydrophobic titanium dioxide nanoparticles. Mixing the two ingredients to accurately control the surface energy in a narrow range and then spray coating, the superhydrophobic and underwater superoleophobic surfaces are conveniently prepared on diverse substrates. Under acid/base aqueous solution conditions, O2 -plasma etching, and sand impingement, the coatings remain superhydrophobic and underwater superoleophobic. Taking advantage of the wettability and robustness of coatings, the as-prepared membranes realize on-demand and multicycle separation under gravity without continuous external stimulus. Importantly, even after 100 sand impingement cycles, the treated membranes still maintain prominent separation performance.